Literasi Digital Calon Guru Sains di Universitas Islam pada Masa Pandemi Covid-19 - Pandu Jati Laksono (Orbital: Jurnal Pendidikan Kimia, 2021)
The covid-19 pandemic has caused changes in learning patterns that lead to technology-based learning activities. Digital literacy in 21st century learning has become inseparable during a pandemic. The purpose of this study was to investigate the digital literacy of prospective science teachers at the Islamic University in Palembang during the Covid-19 pandemic with basic chemistry courses. This study uses a descriptive qualitative method by survey of 100 prospective science teachers in various science-based study programs such as chemistry, biology, and physics. The place of research was carried out at the Islamic University in Palembang. This study uses analysis consist of data reduction, data presentation and drawing conclusions. The results of the study show 1) understanding of digital literacy for science teacher candidates in obtaining 80% theoretical understanding, 30% use of social media, 72% use at home, and 30% use for communication. 2) the description of Belshaw's digital literacy elements is shown with cultural, cognitive, constructive, communicative, creative and critical dimensions in digital literacy. Research conclusions: 1) The theoretical understanding of digital literacy for science teacher candidates is good, mostly for social media, home use and communication. Belshaw's literacy element in digital literacy shows a change in learning patterns towards the digital era on the cultural dimension. Acceleration of access to knowledge on the cognitive dimension. Learning platform that supports the constructive dimension. Ease of communication on the communicative dimension. Constraints in formulating new findings on the creative and critical dimensions.